One-pot, easy and scalable synthesis of large-size short wave length IR emitting PbS quantum dots - Sahu, Umasharan; Prasad, Bhagavatula L. V. (Photochemistry and Photobiology, 2024)
This study presents a versatile and efficient method to synthesize large-size lead sulfide (PbS) quantum dots (QDs) that display emission in the short-wave infrared (SWIR) region, using accessible and stable diethylammonium diethyldithiocarbamate (C-2)(2)DTCA and octylammonium octyldithiocarbamate (C(8)DTCA) as sulfur sources. As these sulfur sources enable the formation of well-dispersed, large-size PbS QDs in a very convenient way, this method can further be taken up for scale-up studies. Importantly, this approach allows precise control over QD sizes, thereby enhancing their SWIR optical properties. By adjusting the hot injection temperatures and sulfur source concentrations, different synthesis routes are explored, providing flexibility for the desired QD characteristics. The results presented here offer a promising opportunity to leverage the synthesized PbS QDs in applications such as optoelectronics, sensors, and imaging technology.
Keywords: hot injection method; Optical properties; quantum dots; short wave IR emission

Strategic design of a single-source precursor for in situ generation and integration of adherent species on Ni3S4 entangled-nanosheets for energy storage applications - Singh, Rahul; Thakur, Rohit; Sahu, Umasharan; Sahoo, Ramesh Chandra; Prasad, Bhagavatula L. V.; Matte, H. S. S. Ramakrishna (ACS Applied Nano Materials, 2025)
Synthesizing transition-metal chalcogenides (TMC) via a single-source precursor (SSP) route has shown great potential due to better reproducibility and control over stoichiometry, phase, and morphology. While the SSP converts into TMC, surfactants or coordinating species are essential to ensure dispersibility for further solution-based processing protocols. These additional species are typically highly toxic, difficult to remove, and adversely affect device performance. Here, as a proof of concept, design-induced in situ stabilized Ni3S4 (DiSNi) protocol demonstrates that strategic SSP design and optimized reaction conditions can facilitate directed chemical reactivity, gradually generating adhering species, which seamlessly integrate onto the metal chalcogenides, aiding the formation of stable dispersions without utilizing additional stabilizers. The proposed mechanism is validated by detailed strategic experiments and analysis, like X-ray photoelectron spectroscopy (XPS), accelerated dispersion stability measurements, and postsynthesis base treatment, which confirm the presence of in situ generated diethylammonium ion (DEA+) as the adherent and corroborate its role in dispersibility. The obtained Ni3S4 entangled-nanosheets are utilized to fabricate additive-free symmetric supercapacitors with organic electrolyte for charge storage over an extended potential window of 2.8 V and an energy density of 12.44 mu W h cm-2 at a power density of 0.42 mW cm-2. The devised DiSNi protocol showcases the importance of the SSP design for achieving multifunctionality. It is anticipated to have a broader impact on the role of careful design of SSP, making it an ideal contender for synthesizing transition-metal chalcogenides.
Keywords: dispersion stability; energy storages devices; low-boiling point solvents; nickel sulfide dispersions; organic electrolyte; single-source precursor; Supercapacitors